Penerapan Kompres Hangat Kayu Manis Pada Penderita Arthritis Gout di Wilayah Kerja Puskesmas Sukoharjo - Rifka Aulia Silviana Putri; Erika Dewi Noorratri (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Background: Indonesia is included in the category of gout arthritis sufferers which is quite high at 35% in the world, while in Central Java it reaches 7.3% while based on symptom diagnosis it is 24.7%, for the prevalence of gout arthritis in Sukoharjo City is 21.04%. The highest number of gout arthritis patients at the Sukoharjo Health Center is 134 sufferers, from the high value of gout arthritis in Indonesia if not treated cause pain and tingling in the joint area. For this reason, efforts are needed to control gout. One of the treatment is to do a warm compress of cinnamon. Purpose: Determine the pain scale before and after the administration of cinnamon warm compresses and see the effect of cinnamon warm compresses on pain in patients with gout arthritis. Method: This type of application uses a descriptive research method and by observing 2 respondents with a history of gout arthritis and given the implementation of a warm cinnamon compress. Result: The scale of pain after being given a warm cinnamon compress is mild pain. Conclusion: There is an effect of giving cinnamon warm compresses on pain in people with gout arthritis.